Relationships between phytoplankton light absorption, pigment composition and size structure in offshore areas of the Mediterranean Sea (Advances in Oceanography and Limnology, 2011)
Phytoplankton absorption is mainly determined by pigment composition and packaging into the cell, in turn affected by pigment concentration and cell size and shape. The variations of the chlorophyll-specific absorption coefficients at two selected wavelengths (443 nm and 675 nm) were analysed for offshore areas of the Mediterranean Sea (Alboran, Algerian, Tyrrhenian, Ionian Basins and Sardinia Channel) investigated in autumn 2006, 2007 and 2008. The spatial distribution of Tchl a, accessory pigments, size structure and taxonomic composition of phytoplankton assemblages was diversified among the areas, characterized by higher contribution of photoprotective pigments in oligotrophic surface waters, while accessory chlorophylls increased in deeper layers and where microphytoplankton dominated. (443) values decreased from the oligotrophic waters to the more mesotrophic ones where microphytoplankton prevailed, while for (675) a small range of variation was observed. The differentiation of (443) was explained by the variations in the phytoplankton assemblage mean cell size, that consequently can be assumed as the main factor determining package effect. Comparison with previous parameterizations supported the existence of a Mediterranean differentiation for which the use of global models might determine inaccuracy for predicting phytoplankton absorption coefficients and thus refining ecological models.
Keywords: Phytoplankton light absorption; package effect; phytoplankton size classes; pigment composition; chlorophyll concentration; Mediterranean Sea